ANALISIS KELAYAKAN POTENSI OBJEK WISATA KAWASAN GUNUNG AMBAWANG MENUJU DESA WISATA BERBASIS MASYARAKAT - Sutarso, Abdullah; Tampubolon, Budiman; Anasih, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to: (1) describe the level of potential tourist attraction area of Mount Ambawang (2) describe the feasibility of the potential of the area of Mount Ambawang, (3) describe people's perceptions of readiness to get to the tourist village, and (4) describe the development of rural tourism based society. This research is a form of qualitative research, which used a sample of 4 (four) objects that exist in the area of Mount Ambawang Ambawang Desa Kubu district, namely; Parong ponds, ponds Puda, junk and Waterfall Batu Bujang Bahar. The method used in this research method qualitative descriptive surve shaped. This research data source community around the village of Kubu district Ambawang Kubu Raya and data on observations and interviews to Ambawang Village community. The results of this study addressing that area of Mount Ambawang Village Ambawang the potential to become a tourist village with a total percentage of 72.5%, about the feasibility of attractions owned by the total percentage is 50%, which means worthy to serve as the area attractions. Then to the public perception of the tourist village is very positive, if dipresentasekan has a total of 84.43%. More on the development of community-based rural tourism is only 45%, which means the development that occurs is not well developed. Then to the public perception of the tourist village is very positive, if dipresentasekan has a total of 84.43%. More on the development of community-based rural tourism is only 45%, which means the development that occurs is not well developed. Then to the public perception of the tourist village is very positive, if dipresentasekan has a total of 84.43%. More on the development of community-based rural tourism is only 45%, which means the development that occurs is not well developed. Keywords: Development of Community-Based Tourism Village,Feasibility Attractions, andPotential Attractions.